Evaluation of diagnostic components and management of childhood pulmonary tuberculosis: a prospective study from Istanbul, Turkey - Aysegul Dogan Demir; Arif Kut; Erhan Ozaydin; Mustafa Nursoy; Fatma Betul Cakir; Feyza Ustabas Kahraman; Ufuk Erenberk; Selcuk Uzuner; Abdulhamit Collak; Zeynep Ebru Cakin; Erkan Cakir (Journal of Infection in Developing Countries)
Introduction: The diagnosis of childhood tuberculosis is difficult and most of the patients are diagnosed clinically. The objective of this study is to reveal the diagnostic and therapeutic components of childhood pulmonary tuberculosis and to analyze the changes that occurred in our country over the years.